The Intersection of Dissemination Research and Acupuncture: Applications for Chronic Low Back Pain - Eric J Roseen DC, MSc; Jonathan Purtle DrPH, MSc; Weijun Zhang DrPH, BMed; David W Miller MD, LAc; Andrea Wershof Schwartz MD, MPH; Shoba Ramanadhan ScD, MPH; Karen J Sherman PhD, MPH (SAGE Publishing, 2021)
Background Dissemination research is the study of distributing information and intervention materials to a specific clinical practice or public health audience. Acupuncture, a healthcare practice involving the stimulation of certain body points, often with thin needles, is considered an evidence-based treatment for low back pain (LBP), but is underutilized in the United States. Body: We will use the example of acupuncture for LBP to identify opportunities to leverage dissemination research to increase utilization of acupuncture. Deficits in the awareness or knowledge of acupuncture may limit its adoption by patients and other stakeholders. Thus, we summarize methods to gather data on stakeholder awareness and knowledge of acupuncture for LBP, i.e., audience research. Engaging multiple stakeholder audiences (e.g., health system leaders, primary care providers, patients), is needed to generate knowledge on promising dissemination strategies for each audience. Audience segmentation is important for identifying population subgroups for whom adoption of acupuncture may require a more intensive or tailored dissemination strategy. To illustrate potential audience 'segments', our research discussion focused on developing dissemination strategies by age (i.e., older adults - those age 65 years or older, and younger adults - those under age 65 ). This decision was prompted by Medicare's recent policy covering acupuncture for chronic LBP. We leverage current knowledge of barriers and facilitators of acupuncture use to discuss how further tailoring of dissemination strategies might optimize adoption of acupuncture in both groups of adults. Experimental study designs could then be used to compare the effectiveness of such strategies to increase awareness, knowledge, or adoption of acupuncture. Conclusions: Conducting dissemination research may improve awareness and knowledge of acupuncture, and ultimately the adoption of acupuncture in biomedical settings. We anticipate that the concepts highlighted in this manuscript will also be helpful for those disseminating information about other complementary and integrative health approaches.